Comparative study on solar flat-plate collectors coupled with three types of reflectors not requiring solar tracking for space heating. (May 2021) - Qiu, Guodong; Ma, Yuanyang; Song, Weiming; Cai, Weihua
Abstract: The existing reflector not requiring solar tracking used in solar flat-plate collector is mainly plate-type structure. This kind of structure is simple, but it is not the optimal one. To solve this problem, the new polyline-type and parabolic-type reflectors not requiring solar tracking were proposed for solar flat-plate collectors in this paper. A comparative study of the two types of reflectors and the existing plate-type reflectors under no sun-tracking conditions was carried out by theoretical and experimental methods. The reflected light losses under the off-design conditions were analyzed. The transient and annual operation characteristics were discussed. The results showed that under the design conditions the ranking of boost factor is parabolic-type, polyline-type and plate-type. But the reflection losses under the off-design conditions are just the opposite. Under the same reflective area with the collectors, when the reflection losses are considered, the increases of solar radiation on the collectors are 40.3%, 27.7% and 19.8% for the polyline, parabolic and flat-plate reflectors respectively in the heating season. In the coldest three months, the polyline-type always has the largest solar radiation. This paper is helpful to improve the efficiency and economy of solar space heating in cold areas. Highlights: Two new reflectors used for flat-plate collector not requiring solar tracking were proposed. Three types of reflectors were comparatively studied by theoretical and experimental methods. The reflectors can ensure low loss of reflected light under no solar tracking conditions. The effect of improving the heat-collecting capacity/temperature is remarkable. Polyline-type reflector has the best performance under the actual conditions.